Investment in antimalarial drug development is bearing fruit - Ashley, E (Elsevier, 2017)
Front-line antimalarial drugs (the artemisinin-based combination therapies) are failing in southeast Asia, making the need for novel antimalarials more pressing than ever. In The Lancet Infectious Diseases, two studies of DSM265, a plasmodium dihydroorotate dehydrogenase inhibitor, are reported. This novel antimalarial, discovered by a team at the University of Texas Southwestern, is in phase 2 clinical development for the prophylaxis and treatment of malaria.